Spectroscopy of organic compounds - Kalsi, P. S. (New Delhi: New Age International, 2004)
The sixth edition of this widely used text includes new examples/spectra/explanations/expanded coverage to update the topic of spectroscopy. The artwork and material in all chapters has been revised extensively for students understanding. New to this edition new discussion and new ir, 1h nmr, 13c nmr and ms spectra. More important basic concepts highlighted and put in boxes throughout this edition. Chapters on 1h nmr and 13c nmr rewritten and enlarged. More on cosy, hetcor, dept and inadequate spectra. A rational approach for solving the structures via fragmentation pathways in mass spectrometry. Increased power of the book by providing further extensive learning material in this revised edition. A quick and an easy access to topics in ugc model curricula. With its comprehensive coverage and systematic presentation the book would serve as an excellent text for b.sc. (hons.) and m.sc. Chemistry students. It provides knowledge to excel at any level, university examination, competitive examinations e.g. Net and before interview boards.
Index 627-631p.
Keywords: Chemical shift; Circularly polarized light; Fragmentation; Isolated double bond; Electromagnetic spectrum